THE SERBIAN ARMY AND ITS STRUGGLE WITH THE AMMUNITION CRISIS OF 1914 - Danilo Šarenac (Istorija 20. Veka, 2024)
The paper discusses the key problem of the Serbian artillery in 1914: the lack of ammunition. The focus of analysis has been placed on the different strategies the Serbian state used to find artillery ammunition and additional weapons. Special attention has been dedicated to the collaboration with France and its shipment of the ’wrong ammunition’ in November 1914. It has been shown that the ammunition crisis was overcome by combining a multitude of resources which included abundant assistance from the Entente, Greece, and the Serbia’s industrial capacities. The problem of the ammunition crisis has been treated as a global phenomenon, enabling placing Serbian theater of operations into a wider perspective.